Prognostic Value of Nonalcoholic Fatty Liver Disease in Patients With Severe Aortic Stenosis Who Underwent Transcatheter Aortic Valve Implantation - Nabeta Takeru; Myagmardorj Rinchyenkhand; Hirasawa Kensuke; Singh Gurpreet K; van der Kley Frank; de Weger Arend; Knuuti Juhani; Bax Jeroen J; Marsan Nina Ajmone; Delgado Victoria (Elsevier, 2023)
Nonalcoholic fatty liver disease (NAFLD) is associated with an increased risk of cardiovascular events. Although the association between NAFLD and aortic valve sclerosis has been described, the prevalence and prognostic implications of NAFLD among patients with severe aortic stenosis (AS) have not been described. In addition, the effect of the presence of severe tricuspid regurgitation (TR) on the prevalence of NAFLD remains unexplored. Accordingly, we investigated the prognostic implications of NAFLD among patients with severe AS with and without concomitant significant TR. A total of 538 patients (aged 80 ± 7 y, 49.6% men) who underwent noncontrast computed tomography before transcatheter aortic valve implantation (TAVI) between 2007 and 2019 were included. NAFLD was defined as a liver-to-spleen attenuation ratio <1.0 on noncontrast computed tomography. NAFLD was present in 118 patients (21.9%). There were no significant differences in pulmonary arterial pressure, right atrial pressure, or the prevalence of significant TR between patients with and without NAFLD. During a median follow-up of 47 months (interquartile range 20 to 70 months), 224 patients (41.6%) died. Univariate Cox regression analysis demonstrated that NAFLD was not significantly associated with all-cause death among patients treated with TAVI (hazard ratio 1.32, 95% confidential interval 0.97 to 1.79, p = 0.07). In conclusion, among patients with severe AS who underwent TAVI, the prevalence of significant TR and the clinical outcomes were similar in patients with and without NAFLD.